MFS1, a Pleiotropic Transporter in Dermatophytes That Plays a Key Role in Their Intrinsic Resistance to Chloramphenicol and Fluconazole - Tsuyoshi Yamada; Takashi Yaguchi; Karine Salamin; Emmanuella Guenova; Marc Feuermann; Michel Monod (Journal of Fungi, 2021)
A recently identified Trichophyton rubrum major facilitator superfamily (MFS)-type transporter (TruMFS1) has been shown to give resistance to azole compounds and cycloheximide (CYH) when overexpressed in Saccharomyces cerevisiae. We investigated the roles of MFS1 in the intrinsic resistance of dermatophytes to CYH and chloramphenicol (CHL), which are commonly used to isolate these fungi, and to what extent MFS1 affects the susceptibility to azole antifungals. Susceptibility to antibiotics and azoles was tested in S. cerevisiae overexpressing MFS1 and ΔMFS1 mutants of Trichophyton benhamiae, a dermatophyte that is closely related to T. rubrum. We found that TruMFS1 functions as an efflux pump for CHL in addition to CYH and azoles in S. cerevisiae. In contrast, the growth of T. benhamiae ΔMFS1 mutants was not reduced in the presence of CYH but was severely impaired in the presence of CHL and thiamphenicol, a CHL analog. The suppression of MFS1 in T. benhamiae also increased the sensitivity of the fungus to fluconazole and miconazole. Our experiments revealed a key role of MFS1 in the resistance of dermatophytes to CHL and their high minimum inhibitory concentration for fluconazole. Suppression of MFS1 did not affect the sensitivity to CYH, suggesting that another mechanism was involved in resistance to CYH in dermatophytes.